Health-related quality of life in adult CHD surgical patients in a low middle-income country: a mixed-methods study. (23rd August 2020) - Ladak, Laila A.; Gallagher, Robyn; Hasan, Babar S.; Awais, Khadija; Abdullah, Ahmed; Gullick, Janice
Abstract: Background and objectives: This mixed-methods study aimed to assess health-related quality of life in young adults with CHD following surgery in a low middle-income country, Pakistan. Despite the knowledge that geographic, cultural and socio-economic factors may shape the way health and illness is experienced and managed and consequently determine a person's health-related quality of life, few health-related quality of life studies are conducted in low middle-income countries. This deficit is pronounced in CHD, so there is little guidance for patient care. Methods: The study utilised concurrent, mixed methods. Adults with CHD (n = 59) completed health-related quality of life surveys (PedsQL TM 4.0 Generic Core Scale, PedsQL TM Cognitive Functioning Scale and PedsQL TM 3.0 Cardiac Module). Semi-structured interview data were collected from a nested sub-sample of 17 participants and analysed using qualitative content analysis, guided by the revised Wilson–Cleary model of health-related quality of life. Results: The lowest health-related quality of life domain was emotional with the mean score (71.61 ± 20.6), followed by physical (78.81 ± 21.18) and heart problem (79.41 ± 18.05). There was no statistical difference in general or cardiac-specific health-related quality of life between mild, moderate or complex CHD. Qualitative findings suggested low health-related quality of life arose from a reduced capacity to contribute to family life including family income and gender. A sense of reduced marriageability and fear of dependency were important socio-cultural considerations. Conclusions: CHD surgical patients in this low-income country experience poor health-related quality of life, and contributing factors differ to those reported for high-income countries. Socio-cultural understandings should underpin assessment, management and care-partnering with young adults with CHD following surgical correction.